The Legal Status Of Land Tenure Of Foreign Nationals Obtained Through Public Auction On The Object Of Mortgage Rights - Patriana Purwa; Geta Ilham Adi Prasetyo; Budi Salman Farizy; Mariam Pratama; Aslan Noor (International Journal of Latin Notary, 2023)
The concept of citizenship stipulates that non-citizens are prohibited from acquiring land ownership in Indonesia, meaning that "only Indonesian citizens are eligible for land ownership rights in Indonesia." This regulation is outlined in Article 21 and Article 26, paragraph (2) of the UUPA. If a foreign national is unable to own land, they are granted land tenure status through auctions, entailing rights of usage or other entitlements. This situation can potentially lead to issues of legal ambiguity and inconsistencies in the regulations governing property rights for foreign nationals who acquire land through auctioned mortgage rights. The primary concern addressed by the author is to determine the status of the auction minutes document as proof of land rights transfer to foreign nationals and the legal status of land rights control held by foreign nationals who obtain property through mortgage rights auctions. The objective of this study is to investigate and analyze the validity of the auction minutes document as evidence of land rights transfer to foreigners and to analyze the legal status of land rights held by foreign nationals who acquire property through mortgage rights auctions. The research employs a normative juridical research method, specifically a normative legal research approach. This approach encompasses both a statutory analysis and a conceptual analysis. Based on the findings of this research: 1. The auction minutes' position as evidence of the transfer of land ownership rights to foreign nationals indicates that these minutes, prepared by the auctioneer, can serve as a valid basis for documenting the transfer of rights to foreign nationals. 2. Regarding the legal status of land ownership obtained by foreign nationals through mortgage rights auctions, it is established that such land ownership is legally valid. Foreign nationals can manage this land under usage rights status, with the utilization rights in the name of foreign nationals being subject to the prescribed rights transfer procedures.